New Bees of the Genera Andrena and Nomada from the Island Cyprus (Hymenoptera: Apoidea), Part II. - Mavromoustakis, George A. (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The author described two new species of bees of the genus Andrena from the island Cyprus (Mediterranean East). These bees are Andrena perapedica, visiting the flowers only of Quercus lusitanica infectoria Oliv., and Andrena hyacinthina, visiting the flowers of Hyacinthus trifoliatus Ten. Of these monolectic bees, the former is related to some Turkestanian species of Andrena and the latter to Andrena apieata Smith. Besides he described the new parasitic bee Nomada kornosica n. sp., which is parasite of Andrena kornosica Mavrom., an endemic species described before from Cyprus. Paratypes from all the above mentioned species were placed in Deutsches Entomologisches Institut, Berlin-Friedrichshagen, Germany. Nomenclatural Actshyacinthina Mavromoustakis, 1958 (Andrena), spec. n.perapedica Mavromoustakis, 1958 (Andrena), spec. n.kornosica Mavromoustakis, 1958 (Nomada), spec. n.